The Spatial Pattern and Distribution of Adansonia Species in the Sahel Savanna Ecosystem of Yobe State, Nigeria - Yahaya Kuku, Ishaya; Jibril Abdullahi, Edicha; Eniyekenimi Daukere, Bitrus; Precious Oru-bo, Jedidiah (Vokasi Unesa Bulletin of Engineering, Technology and Applied Science, 2025)
The study scrutinizes the distribution, of Adansonia species in Southern part of Yobe State Nigeria. A quadrat sampling method was employed for the study and the study area was divided into twenty quadrats using the purposive sampling technique. The quadrat sizes ranges from 100 by 100 meters, 200 by 200 meters, 300 by 300 meters, 400 by 400 meters and 500 by 500 meters. Adansonia species in all 20 quadrats were counted, their species identified. A total of 791 trees were identified in the 20 quadrats out of which 775 are of the species Adansonia digitata while 16 were Adansonia kilima. Furthermore, the nearest neighbor analysis was carried-out to establish the distribution of the said plant in the study area, the result revealed that 19 out of 20 quadrats are dispersed in terms of pattern of distribution with only quadrat 17 exhibiting a random distribution. The result further reveals that out of all the species of Adansonia in the world, only Adansonia digitata and Adansonia kilima are found in the study area, the other species namely Adansonia grandidiera, Adansonia gregorii, Adansonia madagascariensis, Adansonia perrieri, Adansonia rubrostipa, Adansonia suarezensis and Adansonia za were absent in the study area.